Approval of unit price for 500mm dia bored pile work (additional works) - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of unit price for 500mm dia bored pile work (Additional works) of Brac University new campus project.